2011
DOI: 10.3399/bjgp11x548938
|View full text |Cite
|
Sign up to set email alerts
|

Primary care characteristics and population-orientated health care across Europe: an observational study

Abstract: The number of patients with chronic diseases is increasing which poses a challenge to healthcare organisations. A proactive, structured, and populationorientated approach is needed: the chronic care model (CCM) provides such a framework. AimTo assess organisational conditions for providing structured chronic care according to the CCM across different healthcare systems. Design of studyInternational observational study. Setting MethodPractice questionnaires and interviews. Outcome measures were mean practice s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Although there are important differences with regard to the primary care orientation among European countries (van Lieshout et al . ), the primary healthcare sector in Europe is ‘on the move’ (Busse et al . 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are important differences with regard to the primary care orientation among European countries (van Lieshout et al . ), the primary healthcare sector in Europe is ‘on the move’ (Busse et al . 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying theoretical construct of the PACIC is the CCM; a patient centred care approach that is proactive, planned and includes goal setting, problem-solving and follow-up support. Therefore, positive association of patients’ perspectives with practice quality measures can be explained, as the quality indicators of practice organisation and chronic care used during this study could be related to these proactive CCM elements [6]. As patient experience is an important component of quality of care, and patient involvement is central to achieving good outcomes, future research is necessary to specify the constructs of patient assessment instruments that are required to obtain valid and reliable patient judgements of health care processes, particularly if patient experience is used within pay for performance systems [43].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular risk management (CVRM), the majority of which is provided in primary care, includes counselling on lifestyle, preventive medication and continuous monitoring [2,3]. Not all patients suffering from CVD receive optimal care [4,5], which may be related to a range of factors including practice characteristics, and the structure of the care and counselling, which differs considerably across Europe [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Observational research showed that conditions for providing high-quality chronic care differ widely between practice organisations and between countries [6]. This German program to enhance general practice care is in many ways comparable to medical homes in the United States.…”
Section: Discussionmentioning
confidence: 99%